Implementasi Teknologi Augmented Reality Untuk Pembelajaran Sistem Ekskresi Manusia Berbasis Android - Rezkiana, Nisa Tri; Candra, Feri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The development of communication and information technology grows rapidly at this time is very influential in changing people's lifestyle in various fields, such as education. In Academic Atmosphere, especially learning process in Senior High Schools level currently is using the 2013 Curriculum. By following the development of technology can be accepted by students, such as Power Point (PPT) and Three-dimensional (3D) animation that uses interactive mobile devices. One of learning media based on technology is Augmented Reality (AR) technology, this technology combines two-dimensional (2D) or 3D virtual objects into the real-world environment. Inside of it, there is an additional reality that can be applied in all senses, including hearing and senses. In Senior High School Level, one of the subjects is Biology, which a theory that reveals students must use higher understanding level to understand it. That theory is called excretory system in human lung. Implementing Technology Augmented Reality (AR), based on 3D android as the makes students be easyfier to understand hat theory.Keywords: Augmented Reality, Academic Atmosphere, Android, Biology, Excretion System.